The meteorological, hydrological and tidal components of Bosphorus flow - Ozturk, Mehmet; Altas, Furkan (ELSEVIER, 2021)
The Bosphorus is one of the most strategic and busiest waterways in the world connecting the Blacksea to the Mediterranean with the Dardanelles. It presents a two-layer flow structure, and the upper layer flow is incomparably much dynamic than the lower one. In the present study, the short-and longterm components of the upper layer flow were analyzed to quantify the effect of each (tide, river runoff, and meteorological setup) component on the flow structure. For this purpose, the 79 year-long daily-mean Danube River discharges, the 40 year-long European Centre for Medium-Range Weather Forecasts (ECMWF) meteorological model results, the one-year-long water level records at two points, and the current measurements at three points were analyzed. The results revealed that 1) the Danube's springtime influx, which is decisive on the water level difference (Delta eta) between the Blacksea and the Sea of Marmara, shows a large oscillation not only over the long-term period but also at consecutive years and arrives at the Bosphorus within around one month (32 days) delay, 2) Delta eta is highly correlated to the air pressure difference rather than wind speeds during a storm which causes one-layer flow in the strait, 3) there is an increasing trend of extreme meteorological conditions, 4)the astronomical harmonics (e.g M2, S2, etc.) of the tide are weak in the Bosphorus and Solar Annual (Sa) component, which largely occurs due to the heating and cooling cycle (the springtime river runoff cycle), dominates the regular oscillation of tidal component of Delta eta, and 5) the current structure at the southern Bosphorus responds to Delta eta with a 6-h delay while Delta eta responds to air pressure difference with a 12-h delay. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: The Bosphorus; The Danube River; Stratified flow; Exchange flows; Tide; Sea strait; MAXIMAL 2-LAYER EXCHANGE; TURKISH STRAITS SYSTEM; BLACK-SEA; INTERANNUAL VARIABILITY; STRATIFIED FLOWS; WATER EXCHANGE; CONTRACTION; HYDRAULICS; SILL; Environmental Sciences & Ecology; Marine & Freshwater Biology